Assessment of Air Traffic Noise level: A Case Study of Chiang Mai International Airport - Sungtrisearn, Patcharida; Sangsrichan, Chaiwat; Pichayapan, Preda (Journal on Transportation System and Engineering, 2025)
This study aims to analyze the aircraft noise levels at Chiang Mai International Airport and assess the impact of noise pollution on the surrounding areas. The Weighted Equivalent Continuous Perceived Noise Level (WECPNL) index was used as the primary indicator. Noise level measurements were conducted at 6 noise measuring point following the guidelines of the International Civil Aviation Organization (ICAO, 2018) and the Pollution Control Department (2021). The results indicated that the majority of the surrounding areas had noise levels within the standard limits, except for the northern runway end, where the WECPNL value was 70.7, slightly exceeding the standard. This area requires land-use control measures to prevent impacts on the nearby communities. The study also found a correlation between noise levels and factors such as distance from the runway, aircraft takeoff and landing directions, and flight frequency. Spatial data analysis using the Inverse Distance Weighting (IDW) method clearly presented the noise level distribution and can be effectively applied in planning noise management strategies for airport areas. The findings propose various measures to mitigate aircraft noise impacts, such as designing appropriate flight paths, adjusting land-use zones, developing noise-reducing aircraft technologies, and adhering to ICAO guidelines and noise standards set by relevant authorities in Thailand. These measures aim to align with international standards and minimize noise pollution impacts on surrounding communities.